2019
DOI: 10.3390/s19153315
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemiluminescence Sensor Based on Electrospun Three-Dimensional Carbon Nanofibers for the Detection of Difenidol Hydrochloride

Abstract: The detection of difenidol hydrochloride, which is a drug that is widely used for treating the nausea and vomiting symptoms caused by certain diseases, has been increasingly involved in cases of suicide via overdosing and of drug poisoning in children. A novel electrochemiluminescence (ECL) sensor for the simple and effective detection of difenidol hydrochloride was fabricated by modifying a glassy carbon electrode with three-dimensional carbon nanofibers (3D-CNFs). The 3D-CNFs were synthesized by electrospinn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…For instance, Cheng et al demonstrated the synthesis of 3D CNFs by electrospinning a mixture of montmorillonite and PAN, carbonizing the electrospun PNFs, and subsequent acid etching. 36 Tiwari and co-workers presented the synthesis of a highly porous 3D CNF network anchored with Co NPs via combined electrospinning and subsequent post-treatments. 37 Therefore, the electrospinning production of 3D PNFs is the first step and the next step of calcination/carbonization is necessary for the fabrication of 3D CNFs by using the nanofibrous structure of PNFs and the numerous carbon resources of electrospun polymers.…”
Section: Electrospinning Synthesismentioning
confidence: 99%
“…For instance, Cheng et al demonstrated the synthesis of 3D CNFs by electrospinning a mixture of montmorillonite and PAN, carbonizing the electrospun PNFs, and subsequent acid etching. 36 Tiwari and co-workers presented the synthesis of a highly porous 3D CNF network anchored with Co NPs via combined electrospinning and subsequent post-treatments. 37 Therefore, the electrospinning production of 3D PNFs is the first step and the next step of calcination/carbonization is necessary for the fabrication of 3D CNFs by using the nanofibrous structure of PNFs and the numerous carbon resources of electrospun polymers.…”
Section: Electrospinning Synthesismentioning
confidence: 99%
“…When the excited state returns to the ground state [24][25][26], it produces luminescence. The specific reaction process is as shown in formulas ( 1)-( 5) as follows:…”
Section: Ec and Eclmentioning
confidence: 99%
“…CNFs can be grown using a variety of techniques, including electrospinning [8], chemical vapor deposition (CVD) [9] and hot filament assisted sputtering [10]. Plasma enhanced CVD (PECVD) is a widely used method for growing vertically aligned CNFs (VACNFs) at relatively low temperatures.…”
Section: Introductionmentioning
confidence: 99%